(untitled) (Education in the 21st Century, 2025)
Teacher professional development is a continuous process that requires consistent attention from the national education system, teachers, and schools. In today’s educational landscape, teachers who pursue lifelong learning to continuously enhance their professional competencies and skills are most likely to achieve lasting success. This article presents research conducted by a team of Armenian language and literature teachers on the topic of Lesson Study, utilizing the Japanese model. In this approach, the lesson study is led by the participating teachers, with the aim of expanding their professional competencies, skills, and knowledge. The article highlights new and challenging avenues for professional development, and outlines the key components of the Lesson Study model, such as goal setting, collaborative lesson planning (including research planning), lesson delivery, and reflective analysis. Additionally, the article examines the effectiveness of teachers’ professional and expertise-based contributions, focusing on how the applied teaching methods were tracked and refined to improve the instructional process. The findings are based on the outcomes and data from 12 lesson studies. Keywords: lesson study, teacher development target, ability and skill, collaborative planning, teaching and learning, class observation, post-class discussions, reflection and review.